Kewenangan Pengundangan Peraturan Perundang-undangan: Perkembangan Pengaturan dan Peralihan Kewenangan - Sanjaya, Dixon; Erny, Daly (JURNAL USM LAW REVIEW, 2024)
This research was conducted to examine the development of authority to promulgate legislation and its influence on promulgation coordination mechanism. based on Law No. 12/2011, the authority to promulgate is carried out by the Minister of Law and Human Rights. However, after the changes through Law No. 13/2022, this authority is shared with minister for state secretariat. This research seeks to explore the reasons for granting authority to promulgate legislation. This research is doctrinal research using secondary data with a statutory approach. All data is arranged qualitatively. Literature studies show that has been no research specifically analyzes the juridical philosophical basis of the transfer of authority to promulgate legislation. Therefore, this research initiates an investigation into the framework and background to the transfer of authority to promulgate legislations from Indonesian legal policy perspective. The regulation of promulgation authority is influenced by dynamics of government's legal politics. Before the reform, emphasis of promulgation authority was on Ministry of State Secretariat because administrative paradigm. After reform, emphasis of promulgation authority is on Ministry of Law and Human Rights because the legislation paradigm used is substantial. The enactment of Law No. 13/2022 which returns part of promulgation authority to Ministry of State Secretariat is dominated by political factors and causes legislation management system to become ineffective. In improving the governance of promulgating legislation, authority for promulgating legislation needs to be returned to Ministry of Law and Human Rights and government needs to accelerate the formation of a special institution in field of legislation. Penelitian ini dilakukan untuk mengkaji perkembangan kewenangan pengundangan peraturan perundang-undangan dan pengaruhnya terhadap mekanisme koordinasi pengundangan. Hal ini didasarkan pada ketentuan UU 12/2011 dimana kewenangan pengundangan dilakukan menteri hukum dan HAM. Akan tetapi, pasca perubahan peraturan melalui UU 13/2022, kewenangan tersebut dibagi bersama menteri sekretariat negara. Penelitian ini berupaya menggali landasan substansial yang melandai peralihan kewenangan pengundangan tersebut. Penelitian ini berupa penelitian doktrinal yang menggunakan data sekunder dengan pendekatan peraturan perundang-undangan. Seluruh data disusun secara kualitatif. Studi literatur menunjukan belum ada penelitian yang secara khusus menganalisis peralihan kewenangan pengundangan peraturan perundang-undangan di Indonesia. Oleh karenanya, penelitian ini menginisiasi penelusuran kerangka berpikir dan latar belakang pengalihan kewenangan pengundangan peraturan perundang-undangan dalam perspektif politik hukum Indonesia. Pengaturan kewenangan pengundangan sangat dipengaruhi dinamika ketatanegaraan dan politik hukum pemerintah. Sebelum reformasi, titik berat kewenangan pengundangan pada Kemensetneg berdasarkan paradigma prosedural dan administratif. Setelahnya, titik berat kewenangan pengundangan pada Kementerian Hukum dan HAM karena paradigma peraturan perundang-undangan yang digunakan bersifat substansial. Berlakunya UU 13/2022 yang mengembalikan sebagian kewenangan pengundangan kepada Kemensetneg didominasi oleh faktor politis dan menyebabkan sistem pengelolaan pengundangan menjadi tidak efektif. Dalam membenahi tata kelola pengundangan peraturan perundang-undangan, maka kewenangan pengundangan tersebut perlu dikembalikan kepada Kemenkumham dan pemerintah perlu mempercepat pembentukan lembaga khusus bidang peraturan perundang-undangan.